(untitled) (Revista Brasileña de Ciencias Policiales, 2026)
This article seeks to clarify the effectiveness of the Rukun Warga (RW) Police policy. The issue originates from the Indonesian National Police’s deployment of Community Police (Polisi Masyarakat), which is carried via the RW Police, as a way of proactively addressing security concerns and maintaining public order. It also serves as an instrument for early problem detection within the community and functions as a localized problem-solving entity. The establishment of RW Police represents a strategic initiative to bolster bureaucratic efficiency, specifically within the realm of public services, while also embodying alignment with Indonesia’s indigenous wisdom and cultural values. However, the strategy to establish RW Police to improve public services is less effective in practice, owing to several challenges. These challenges include an inadequate number of RW Police personnel, insufficient facilities and infrastructure support for RW Police units, and adding to the difficulty is the concurrent assignment of several police officers to both the RW Police and the Resort Police. Because of this combination of factors, the communication between the RW Police and the local population has been disrupted. The obstacle posed by ineffective RW Police policy implementation in resolving on-the-ground difficulties severely reduces the Indonesian National Police’s utilization of the RW Police as an instrument for improving public services.